2018
DOI: 10.3892/or.2018.6208
|View full text |Cite
|
Sign up to set email alerts
|

CLDN5 affects lncRNAs acting as ceRNA dynamics contributing to regulating blood‑brain barrier permeability in tumor brain metastasis

Abstract: The blood‑brain barrier (BBB) constitutes an efficient organization of tight junctions that limits the delivery of tumor to the brain. The principal tight junction protein in BBB is claudin‑5 (CLDN5), but its mechanism of action remains largely unknown. Long non‑coding RNAs (lncRNAs) are aberrantly expressed in many cancers, some lncRNAs play key roles in regulating BBB permeability and are involved in tumor brain metastasis. In particular, lncRNAs can function as competing endogenous RNAs (ceRNAs). Herein, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Ma discovered CLDN5 was closely related to brain metastases from lung cancer [33]. In 2019, Jia indicated that high-dose bevacizumab likely increased lung tumor invasion and potential metastatic abilities through down-regulating CLDN5 [34].Moreover, CLDN5 showed a close relationship with mental illness, such as depression [35], schizophrenia [36], brain edema following fatal heat stroke [37] and tumor brain metastasis [38]. showed that PECAM1 was found to be related to angiogenesis of the lung cancer [39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Ma discovered CLDN5 was closely related to brain metastases from lung cancer [33]. In 2019, Jia indicated that high-dose bevacizumab likely increased lung tumor invasion and potential metastatic abilities through down-regulating CLDN5 [34].Moreover, CLDN5 showed a close relationship with mental illness, such as depression [35], schizophrenia [36], brain edema following fatal heat stroke [37] and tumor brain metastasis [38]. showed that PECAM1 was found to be related to angiogenesis of the lung cancer [39][40].…”
Section: Discussionmentioning
confidence: 99%
“…There are several obstacles facing the development of lncRNA-based therapeutics for IAs. One of the obstacles impeding development of lncRNA-based therapeutics is low delivery efficacy to the brain vasculature and the likely need for repeated delivery [68]. Second, the functions and mechanisms used by lncRNAs are much more complex and diversified than other non-coding RNAs [3].…”
Section: Lncrna-based Therapeuticsmentioning
confidence: 99%
“…Fourthly, challenges for lncRNAs delivery remain with respect to their efficiency and tissue specificity [70]. While viral vectors induce immunogenicity, challenges for delivery lncRNAs may be overcome using chemical functionalization of nanoparticles surface targeted to specific ligands overexpressed by cells in the cerebral vessel wall in response to relevant stimuli [68,71]. In addition, most lncRNAs lack conservation between species, which restricts the utility of preclinical animal models.…”
Section: Lncrna-based Therapeuticsmentioning
confidence: 99%
“…microRNA-143, -146a, -149-5p, -21, -96 and -155 [3136]). Interestingly, in addition, Ma et al [37] found that claudin-5 affects the expression of long non-coding RNAs (lncRNAs) in brain endothelial cells thereby regulating BBB properties in brain metastases.…”
Section: Brain Endotheliummentioning
confidence: 99%